PENERAPAN INSOLVENCY TEST DALAM HUKUM INDONESIA : STUDI PUTUSAN PAILIT DI INDONESIA - , Hendy Akhmadi, Dr. Paripurna, S.H., M.Hum., LL.M ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This legal research are aims to knowing how to Insolvency Test in United States Applicated to determine the Debts are in insolven area and can be bankrupted. As the object in this legal research use the Indonesia Commericial Code Decisions, the purpose is to knowing how the judges makes the decisions is that use Insolvency Test like in United States or just by Article 2 paragraph ( 1 ) of Law No. 37 of 2004 on Bankruptcy and Suspension of Payment The method used in this study is a normative research methods to the type of library research. The object of research used in this study is the decision of the commercial court in Indonesia and compare the bankruptcy law in Indonesia and in the United States, especially regarding evidence against the defendant debtor bankrupt . The results of research in the can is that in the United States, the debtor declared insolvent if it has met Insolvency Test that has been used is the Balance Sheet Test, Test Equity, and Transactional Test. While in Indonesia, the debtor is declared bankrupt if he has proved simple seceara not pay off the debt first due and collectible as well as having other creditors, did not consider whether the amount of their wealth is greater than the amount of debt or otherwise .